Challenges of Digital Literacy Education in Pandemic Period - Chaterina Puteri Doni; Dahlia Husain; Sriwahyuningsih R Saleh; Nurul Aini Pakaya; Cutri A Tjalau; Berti Arsyad (Journal of Education Review Provision, 2021)
The Covid-19 pandemic that has hit the world has had an impact in various fields including education. The application of teaching and learning from home forces educational institutions to switch to digital in implementing learning. The application of learning methods online provides new experiences in current learning methods. Various community responses are present. in response to this relatively new learning system. Rapid digital development and the current emergency situation demands that all stakeholders and all walks of life must adjust to developments. This is of course a common concern in providing solutions to existing problems, so that even in a pademi situation the teaching and learning process can still run smoothly. Digital literacy needs to be carried out extensively (starting from family, school and society), so that all these elements can not only use technology but can also make good and efficient use of it. This research uses a descriptive analysis method. The purpose of this research is to describe related media use. digital, in this case digital literacy, which can be used as an important key in the successful implementation of learning online during a pandemic.